Hepatic rather than cardiac steatosis relates to glucose intolerance in women with prior gestational diabetes. - Yvonne Winhofer (Public Library of Science (PLoS), 2014)
Background Increased myocardial lipid accumulation has been described in patients with pre- and overt type 2 diabetes and could underlie the development of left-ventricular dysfunction in metabolic diseases (diabetic cardiomyopathy). Since women with prior gestational diabetes (pGDM) display a generally young population at high risk of developing diabetes and associated cardiovascular complications, we aimed to assess whether myocardial lipid accumulation can be detected at early stages of glucose intolerance and relates to markers of hepatic steatosis (Fatty Liver Index), cardiac function, insulin sensitivity and secretion. Methods Myocardial lipid content (MYCL), left-ventricular function (1H-magnetic-resonance-spectroscopy and -imaging), insulin sensitivity/secretion (oral glucose tolerance test) and the fatty liver index (FLI) were assessed in 35 pGDM (45.6±7.0 years, 28.3±4.8 kg/m2) and 14 healthy control females (CON; 44.7±9.8 years, 26.1±2.5 kg/m2), matching for age and body-mass-index (each p>0.1). Results Of 35 pGDM, 9 displayed normal glucose tolerance (NGT), 6 impaired glucose regulation (IGR) and 20 had been already diagnosed with type 2 diabetes (T2DM). MYCL and cardiac function were comparable between pGDM and CON; in addition, no evidence of left-ventricular dysfunction was observed. MYCL was inversely correlated with the ejection fraction in T2DM (R = -0.45, p<0.05), while the FLI was tightly correlated with metabolic parameters (such as HbA1C, fasting plasma glucose and HDL-cholesterol) and rose along GT-groups. Conclusions There is no evidence of cardiac steatosis in middle-aged women with prior gestational diabetes, suggesting that cardiac complications might develop later in the time-course of diabetes and may be accelerated by the co-existence of further risk factors, whereas hepatic steatosis remains a valid biomarker for metabolic diseases even in this rather young female cohort.